Secure anonymous mutual authentication for star two-tier wireless body area networks. Issue 135 (October 2016) - Ibrahim, Maged Hamada; Kumari, Saru; Das, Ashok Kumar; Wazid, Mohammad; Odelu, Vanga
Highlights: We propose a new secure protocol for star topology two-tier wireless body area networks. The proposed protocol is shown secure using the widely-accepted BAN logic, and also through rigorous informal security analysis. To demonstrate the practicality of our protocol, we evaluate it using NS-2 simulator. Abstract: Background and objectives: Mutual authentication is a very important service that must be established between sensor nodes in wireless body area network (WBAN) to ensure the originality and integrity of the patient's data sent by sensors distributed on different parts of the body. However, mutual authentication service is not enough. An adversary can benefit from monitoring the traffic and knowing which sensor is in transmission of patient's data. Observing the traffic (even without disclosing the context) and knowing its origin, it can reveal to the adversary information about the patient's medical conditions. Therefore, anonymity of the communicating sensors is an important service as well. Few works have been conducted in the area of mutual authentication among sensor nodes in WBAN. However, none of them has considered anonymity among body sensor nodes. Up to our knowledge, our protocol is the first attempt to consider this service in a two-tier WBAN. We propose a new secure protocol to realize anonymous mutual authentication and confidential transmission for star two-tier WBAN topology. Methods: The proposed protocol uses simple cryptographic primitives. We prove the security of the proposed protocol using the widely-accepted Burrows-Abadi-Needham (BAN) logic, and also through rigorous informal security analysis. In addition, to demonstrate the practicality of our protocol, we evaluate it using NS-2 simulator. Results: BAN logic and informal security analysis prove that our proposed protocol achieves the necessary security requirements and goals of an authentication service. The simulation results show the impact on the various network parameters, such as end-to-end delay and throughput. The nodes in the network require to store few hundred bits. Nodes require to perform very few hash invocations, which are computationally very efficient. The communication cost of the proposed protocol is few hundred bits in one round of communication. Due to the low computation cost, the energy consumed by the nodes is also low. Conclusions: Our proposed protocol is a lightweight anonymous mutually authentication protocol to mutually authenticate the sensor nodes with the controller node (hub) in a star two-tier WBAN topology. Results show that our protocol proves efficiency over previously proposed protocols and at the same time, achieves the necessary security requirements for a secure anonymous mutual authentication scheme.